2009
DOI: 10.1017/s002531540900068x
|View full text |Cite
|
Sign up to set email alerts
|

Larval and early post-larval morphology, growth, and behaviour of laboratory reared Lopholithodes foraminatus (brown box crab)

Abstract: The larval and post-larval behaviour, growth, colour, and morphology of the brown box crab (Lopholithodes foraminatus) are described for the first time based on laboratory reared animals. A detailed morphological description is provided for 4 zoeal stages, the glaucothoe, and the first crab instar. Selected morphological changes over the remainder of the first year of development are also described. Data are presented on larval growth at 11°C and on zoeal stage durations at approximately 8°C, 12°C and 16°C. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Capture and husbandry details and larval rearing methodologies are described in Duguid and Page (2009). If not otherwise specified, zoeae were reared either in 1 l glass beakers or 4 l plastic buckets at approximately 111C.…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Capture and husbandry details and larval rearing methodologies are described in Duguid and Page (2009). If not otherwise specified, zoeae were reared either in 1 l glass beakers or 4 l plastic buckets at approximately 111C.…”
Section: Overviewmentioning
confidence: 99%
“…In the course of rearing work to describe the development of Lopholithodes foraminatus (Stimpson 1859) (brown box crab), I observed that a significant proportion of glaucothoe and early juvenile instars had a larger left claw (Duguid and Page 2009). I also captured a brooding female of L. foraminatus exhibiting reversed asymmetry of both the abdomen and chelae.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations